Determination of benzoic acid in fermented fish products using HPLC / Norlida Baharudin - Baharudin, Norlida (2009)
Food fermentation is a widespread traditional technology which has been improved into more sophisticated industries. The fermented fish products have two characteristics, solid and semi-solid. Belacan is the example of solid and the examples of semi-solid are budu and cencaluk. Benzoic acid was used in fermented fish products as a preservative. It is used to prevent growth of yeast and mould, being also effective against a wide range of bacteria. It was analysed using High Performance Liquid Chromatography (HPLC) using two mobile phase (MP) systems. The mobile phase system (MP I) used are methanol-glacial acetic acid-water (35: 5: 60) with detection of 245 nm and mobile phase system (MP II) are methanol-0.01M ammonium acetate buffer with detection of 235 nm. For mobile phase I, the amount of benzoic in cencaluk was found to be 2609 ppm and the amount of benzoic acid in budu and belacan was found to be unavailable for detection. While for mobile phase II, the amount of benzoic acid was found to be absent at the all samples. The level of benzoic acid in cencaluk was apparently higher than the permissible level of 750 ppm according to Malaysian Food and Agricultural Import Regulations and Standards, Country Report (2004).